2019
DOI: 10.1103/physrevb.100.165405
|View full text |Cite
|
Sign up to set email alerts
|

Ni-based transition metal trichalcogenide monolayer: A strongly correlated quadruple-layer graphene

Abstract: We investigate the electronic physics of layered Ni-based trichalcogenide NiPX3 (X=S, Se), a member of transition-metal trichalcogenides (TMTs) with the chemical formula, ABX3. These Ni-based TMTs distinguish themselves from other TMTs as their low energy electronic physics can be effectively described by the two eg d-orbitals. The major band kinematics is characterized by the unusal long-range effective hopping between two third nearest-neighbor (TNN) Ni sites in the two-dimensional Ni honeycomb lattice so th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…However, the degree of the structural distortion would seem to be far too small to result in a difference of %1 meV observed in Table I. The assumption is supported by ab initio calculations 22,23 which calculated magnetic exchange parameters for energetically relaxed structures. Consistent with observations, the calculated structures were only very slightly distorted and the calculations gave unique exchange parameters for nominally equivalent nearestneighbors which, depending on the magnitude of the on-site repulsion term, were comparable to those of Lançon et al…”
Section: Discussionmentioning
confidence: 83%
“…However, the degree of the structural distortion would seem to be far too small to result in a difference of %1 meV observed in Table I. The assumption is supported by ab initio calculations 22,23 which calculated magnetic exchange parameters for energetically relaxed structures. Consistent with observations, the calculated structures were only very slightly distorted and the calculations gave unique exchange parameters for nominally equivalent nearestneighbors which, depending on the magnitude of the on-site repulsion term, were comparable to those of Lançon et al…”
Section: Discussionmentioning
confidence: 83%
“…Among magnetic MPX 3 , NiPS 3 particularly exhibits intriguing quantum properties owing to the presence of strong charge-spin correlation effects ( 15 , 22 , 26 , 27 ). It shows zigzag antiferromagnetism with weak in-plane anisotropy below T N ~155 K, in which ferromagnetically arranged spin chains are antiferromagnetically coupled throughout the crystal lattice down to bilayer stacking.…”
Section: Introductionmentioning
confidence: 99%
“…Low-temperature optical conductivity measurements revealed that these intersite transitions are allowed only between AFM Ni neighbors and demonstrated strong correlation between electronic and magnetic structures in NiPS 3 ( 22 ). Notably, NiPS 3 is the only known magnetic vdW material that exhibits NCT ground state with a close resemblance to the hole-doped high-temperature cuprate superconductors ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under the slave boson mean-field approach, we study superconducting pairings in the hole doped three-orbital model. Due to the high degeneracy of the three t 2g orbitals, the carrier occupancies in the three orbitals are identical, leading to an equal renormalization factor for all the hopping interactions [32]. The results are reported in Fig.4.…”
mentioning
confidence: 94%
“…We use the slave boson mean-field approach [20,[30][31][32]] to calculate the superconducting states in the hole doped region. The results are reported in Fig.2 with J/t = 0.3 in (a,b) and J/t = 0.5 in (c,d), respectively.…”
mentioning
confidence: 99%